Diagnostic performance of different imaging modalities in the assessment of distant metastasis and local recurrence of tumor in patients with non‐small cell lung cancer. Issue 6 (17th April 2017) - Ohno, Yoshiharu; Yoshikawa, Takeshi; Kishida, Yuji; Seki, Shinichiro; Koyama, Hisanobu; Yui, Masao; Kassai, Yoshimori; Aoyagi, Kota; Kaminaga, Shigeo; Sugimura, Kazuro
Abstract : Purpose: To compare the diagnostic performance of positron emission tomography with [18F] fluoro‐2‐deoxy‐glucose (FDG‐PET) coregistered with magnetic resonance imaging (FDG‐PET/MRI), MRI with and without diffusion‐weighted imaging (DWI), FDG‐PET fused with computed tomography (FDG‐PET/CT) with brain contrast‐enhanced (CE‐) MRI, and routine radiological examination for assessment of postoperative recurrence in nonsmall‐cell lung cancer (NSCLC) patients. Materials and Methods: 96 consecutive postoperative NSCLC patients (52 men, 44 women; mean age 72 years) prospectively underwent whole‐body 3T MRI with and without DWI; PET/CTs and routine radiological examinations consisted of CE‐brain MRI, whole‐body CE‐CT, and bone scintigraphy. The patients were divided into a recurrence ( n = 17) and a nonrecurrence ( n = 79) group based on pathological and follow‐up examinations. All coregistered PET/MRIs were generated by proprietary software. The probability of recurrence was visually assessed on a per‐patient basis. Receiver operating characteristic analyses were used to compare the diagnostic performance of all methods. Finally, diagnostic capabilities were compared by means of McNemar's test. Results: Areas under the curves (Azs) were significantly larger for PET/MRI and whole‐body MRI with DWI (Az = 0.99) than for PET/CT (Az = 0.92, P < 0.05) and conventional radiological examination (Az = 0.91, P < 0.05). Specificity and accuracy of PET/MRI and MRI with and without DWI were significantly higher than those of PET/CT ( P < 0.05) and routine radiological examination ( P < 0.05). Conclusion: Whole‐body FDG‐PET/MRI and MRI with DWI were found to be more specific and accurate than FDG‐PET/CT and routine radiological examinations for assessment of recurrence in NSCLC patients, although MRI with and without DWI demonstrated slightly lower sensitivity than PET/CT. Level of Evidence: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2017;46:1707–1717.